Municipal waste management systems for domestic use. (15th November 2017) - Jouhara, H.; Czajczyńska, D.; Ghazal, H.; Krzyżyńska, R.; Anguilano, L.; Reynolds, A.J.; Spencer, N.
Abstract: Every year, the average citizen of a developed country produces about half a tonne of waste, thus waste management is an essential industry. Old waste management systems based on the collection of mixed/sorted waste and transporting it a long way to disposal sites has a significant negative impact on the environment and humans. This paper will review the available waste management systems for households. Biological methods (such as composting or anaerobic digestion) and physicochemical methods (such as burning or pyrolysis) of waste utilization will be considered from the householder's point of view. The most important features of each system will be discussed and compared. Municipal waste management systems for domestic use could eliminate or significantly reduce the stage of waste collection and transportation. Additionally, they should not require special infrastructure and at the same time should allow garbage to be changed into safe products or energy sources with no harmful emissions. The aim of the work is to identify the best available waste disposal systems for domestic use. Highlights: Waste management systems at source - in the household- is reviewed. Biological methods are relatively cheap, but their effectiveness is limited. Pyrolysis and gasification allow to fully utilize almost all waste at home.